2019
DOI: 10.1007/978-3-030-25543-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Verification of Network Fault Tolerance via Counterexample-Guided Refinement

Abstract: We show how to verify that large data center networks satisfy key properties such as all-pairs reachability under a bounded number of faults. To scale the analysis, we develop algorithms that identify network symmetries and compute small abstract networks from large concrete ones. Using counterexample guided abstraction refinement, we successively refine the computed abstractions until the given property may be verified. The soundness of our approach relies on a novel notion of network approximation: routing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Then, the time of verification programming may be out of control. Though some tools aim to improve the efficiency of verifying the reachability of the network by compressing the scale of the large network [19] or abstracting the control plane in a systematic form [15], they are obviously at the cost of losing the possibility of verifying QoS network properties. Therefore, it is still a significant and challenging issue to model and encode the network concisely and concretely.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the time of verification programming may be out of control. Though some tools aim to improve the efficiency of verifying the reachability of the network by compressing the scale of the large network [19] or abstracting the control plane in a systematic form [15], they are obviously at the cost of losing the possibility of verifying QoS network properties. Therefore, it is still a significant and challenging issue to model and encode the network concisely and concretely.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The operates on the routes in lexicographic order. In other words, can be treated as the total order that ranks and models the routing decision procedure using some combination of record fields [19], [20]. For example, if a router receives two records of different protocols, we just compare the ad values of the two records to obtain a better one.…”
Section: B Abstract the Graph To Algebra Structurementioning
confidence: 99%
“…(1) high branching factors (e.g., conditionals with many branches because there are many different possible destinations) [Beckett et al 2019a;Giannarakis et al 2020], and (2) many symmetries (e.g., topologies used in datacenters are highly symmetric in part to tolerate failures; and many destinations may share common processing components and generate similar routes) [Beckett et al 2018;Giannarakis et al 2019Giannarakis et al , 2020Plotkin et al 2016] (3) a large number of simple, repeated computations.…”
Section: Efficient Symbolic Simulationmentioning
confidence: 99%
“…Perhaps, the surprising part is that the simulation struggles the most with datacenter networks. Prior work [Giannarakis et al 2019[Giannarakis et al , 2020 suggested that networks with highly symmetric designs, such as Fat Trees, are amenable to fault-tolerance analyses due to their high degree of redundancy. However, in our case, simulation fails to compute routes even for a relatively small Fat Tree network with 216 links Ðthese networks can scale to hundreds of nodes and several thousand links.…”
Section: Verification Performancementioning
confidence: 99%
“…In verification of computer networks, however, the properties to be verified usually concern delivery of packets rather than the functioning of the algorithm implemented by the network. Symmetries in computer networks were used to simplify formal verification in [38]- [40].…”
Section: Related Workmentioning
confidence: 99%